1992
DOI: 10.1111/j.1526-4610.1992.hed3209461.x
|View full text |Cite
|
Sign up to set email alerts
|

Flunarizine in Migraine: A Double‐blind Placebo‐controlled Study (in a Saudi Population)

Abstract: We evaluated the effect of flunarizine (Fz) (10 mg/d) on migraine in a double-blind placebo-controlled design. The attacks' frequency, duration, severity and associated symptoms were compared before and after treatment. Forty-two patients completed a three-month trial period; 21 patients received Fz and 21 placebo. Statistical analysis showed no significant difference between Fz and placebo (p > 0.05). In this study Fz was not more efficient than placebo in migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The AHCPR Technical Report identified 45 controlled trials of calcium antagonists, including flunarizine (25 trials), nimodipine (11 trials), nifedipine (five trials), verapamil (three trials), cyclandelate (three trials), and nicardipine (one trial) (10). Flunarizine was compared with placebo in eight migraine prevention trials and effect sizes could be calculated for seven studies (107–113) but not the eighth study (114). A meta‐analysis of these seven heterogeneous trials was statistically significant in favour of flunarizine.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…The AHCPR Technical Report identified 45 controlled trials of calcium antagonists, including flunarizine (25 trials), nimodipine (11 trials), nifedipine (five trials), verapamil (three trials), cyclandelate (three trials), and nicardipine (one trial) (10). Flunarizine was compared with placebo in eight migraine prevention trials and effect sizes could be calculated for seven studies (107–113) but not the eighth study (114). A meta‐analysis of these seven heterogeneous trials was statistically significant in favour of flunarizine.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Although there are 7 double-blind, randomized, placebocontrolled studies in which flunarizine, in a single nocturnal dose of 10 mg, was shown to reduce the frequency, the duration, and the intensity of migraine attacks, these studies do not present the necessary requirements to categorize this finding as Level A evidence due to various factors, especially the low number of subjects studied. 32,[52][53][54][55][56][57] Three meta-analysis studies corroborate the positive results from primary outcomes, [58][59][60] with the caveat in one of them 60 that the decrease in the frequency of headache attacks would take place at weeks 8, 12, 16, and 20, but not in week 4.…”
Section: Studiesmentioning
confidence: 69%
“…Although there are 7 double-blind, randomized, placebo-controlled studies in which flunarizine, in a single nocturnal dose of 10 mg, was shown to reduce the frequency, the duration, and the intensity of migraine attacks, these studies do not present the necessary requirements to categorize this finding as Level A evidence due to various factors, especially the low number of subjects studied. 32 52 53 54 55 56 57…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…Most of the outcome measures used in our trial were based on patient’s subjective feelings and there weren’t many objective indicators. Besides, a daily dose of 5 mg flunarizine was a relatively low dose compared with the previous studies [ 38 , 39 ] which may have led to a modest improvement in the efficacy outcome measures of migraine. Ten milligram flunarizine may guarantee a more rapid efficacy [ 40 ].…”
Section: Discussionmentioning
confidence: 83%